Did Home-Based Exams during COVID-19 Affect Student Ranking? A Case from a Business School - Leiv Opstad, Ivar Pettersen (Educational Process: International Journal)
Background/purpose – Home-based exams were introduced during COVID-19 with an open-book format and limited control over dishonest student behavior. Such exams were used in lieu of traditional, closed-book school-based exams as a necessity due to the pandemic. This article investigates whether or not students’ grades from home-based assessment exams differed from the grades they achieved in traditional school-based exams.